IMPACT OF FACILITY MAINTENANCE SYSTEM ON PRODUCT PHYSICAL LOSSES IN A POULTRY FEED MILL UNIT - CORADI, P. C.; LACERDA FILHO, A. F. de; CHAVES, J B. P. (Revista Brasileira de Engenharia de Biossistemas, 2011)
The aim of the study was to evaluate the quantitative, the costs and contaminations of the physical losses of products caused by maintenance system utilized on the equipments of the different stages of production of a feed mill. The experiment was conducted in a feed industry with capacity of production of 1,000 ton.day-1. Firstly, a rising of the maintenance system used in the feed mill was done, after the products losses were quantified in the external and internal sectors of the milling steps. Two methods were utilized for losses quantification: per sector and per equipment of the feed industry. Samples of the products were collected in different points of area evaluated for counting of fungi and salmonellas colonies, whole and fragments insects and mites. The results showed a high number of maintenances not performed within the programmed period, arriving to 70%. In addition, the equipments maintenance system utilized in the feed milling, significantly influenced in the products losses, arriving to 120 Kg and costs of US$ 38 per hour worked. The microbiology analysis presented a high contamination index (7.4x104 CFU.g-1) in the final products.